THE EFFECT OF GIVING MANGO LEAF BOILING ON REDUCING URIC ACID LEVELS IN ELDERLY IN PMB NY. R GANDUL CINERE DEPOK YEAR 2023 - Siti Nur Halimah; Vivi Silawati; Putri Azzahroh (Rajaki of Tulip Medika Publisher, 2024)
If purine intake from food is too high, exceeding 15% of the body's needs, there will be a buildup of purine in the body. Foods that contain high levels of purine cause uric acid levels to rise in the body. In Indonesia, the prevalence of gout at ages 55-64 years is around 45%, and at ages 65-74 years is around 51.9%, and at ages >75 years is around 54.8%. The prevalence of gout arthritis in Indonesia in 2018 was around 11.9%, with Aceh at 18.3%, West Java at 17.5%, and Papua at 15.4%. Based on the symptoms of gouty arthritis in East Nusa Tenggara, it is 33.1%, West Java is 32.1%, and Bali is also 30%. According to one study, increasing uric acid levels in the blood, apart from causing gout, is a strong predictor of death due to cardiovascular damage. The aim of this research was to determine the effect of giving boiled mango leaves on reducing uric acid levels in PMB Ny. R Gandul Cinere Depok 2023. Type pThe research used was an experiment with Quasy Experiment using a one group Pre-Post test design approach. The population in this study was 30 menopausal elderly people. Data analysis used the Shapiro Wilk test and Wilcoxon test.The results of the analysis research show that the average pretest before given boiled mango leaves, namely 7.233 and the average posttest score after being given boiled mango leaves was 5.257with a significant p-value = 0.000. ConclusionThere is an effect of giving boiled mango leaves on uric acid levels in menopausal elderly in PMB Ny. R Gandul Cinere Depok in 2023.